Analisis Tindak Tutur Ilokusi dalam Film ‘Sekawan Limo’ karya Bayu Skak - Dina Arifna Hidayah; Ghozy Fais Yanuar Zain; Dyah Ayu Novitasari; Aleiya Nabila; Krisnawati Hayuningtyas; Maulana Febryan Saputra; Asep Purwo Yudi Utomo; Hidayatun Nur (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Illocutionary speech are one of the key concepts in pragmatics, referring to actions performed by the speaker through utterances with specific intentions and functions. Illocutionary acts are a central aspect of speech act theory and are categorized into five types, namely expressive, declarative, representative, directive, and commissive acts. This study examines illocutionary acts in the film Sekawan Limo by Bayu Skak. The aim of this research is to analyze how illocutionary acts create additional meaning in communication between characters, as well as to understand how these acts influence the development of the storyline and character progression within the film. The data collection techniques used in this research include a descriptive qualitative approach, along with matching methods, observation and note-taking, as well as formal and informal methods.Based on the findings, we identified inaccuracies or misuses in illocutionary acts, including expressive, declarative, representative, directive, and commissive types. The benefit of this research lies in the development of scientific knowledge and understanding regarding illocutionary acts. For the general public, this study can provide insight into the various types of illocutionary acts. Through this research, we hope to deepen the understanding of illocutionary acts and provide useful information that can serve as a valuable reference for future researchers conducting similar studies.